Antiretroviral therapy reduces but does not normalize immune and vascular inflammatory markers in adults with chronic HIV infection in Kenya. (1st January 2021) - Temu, Tecla M.; Zifodya, Jerry S.; Polyak, Stephen J.; Wagoner, Jessica; Wanjalla, Celestine N.; Masyuko, Sarah; Nyabiage, Jerusha; Kinuthia, John; Bloomfield, Gerald S.; Page, Stephanie T.; Farquhar, Carey
Abstract : Introduction: Markers of monocyte/macrophage activation and vascular inflammation are associated with HIV-related cardiovascular diseases (CVD) and mortality. We compared these markers among African people living with HIV (PLWH) and HIV-negative adults, and examined risk factors associated with elevated biomarkers (>75th percentile) in PLWH on antiretroviral therapy (ART). Design: Cross-sectional study. Methods: We measured serum concentrations of a gut integrity biomarker (intestinal-fatty acid binding protein), monocyte/macrophage activation biomarkers (soluble CD14 and CD163), and vascular inflammation biomarkers [soluble intercellular adhesion molecule 1 (sICAM-1) and soluble vascular adhesion molecule 1 (sVCAM-1)]. We assessed the relationship of these inflammatory parameters with HIV, using logistic regression adjusting for traditional CVD risk factors. Results: Among the 541 participants, median age was 43 years and half were female. Among 275 PLWH, median CD4 + T-cell count and duration of ART use was 509 cells/μl and 8 years, respectively. PLWH had significantly higher prevalence of elevated inflammatory biomarkers compared with HIV-negative individuals even after adjustment for traditional CVD risk factors. Compared with individuals without HIV, the prevalence of elevated biomarkers was highest among persons with detectable viral load and CD4 + T-cell counts 200 cells/μl or less. In a subanalysis among PLWH, nadir CD4 + T-cell count 200 cells/μl or less was associated with elevated soluble CD14 (sCD14); dyslipidemia with elevated sCD14, sICAM-1, and sVCAM-1; and overweight/obesity with reduced sCD14. Longer ART exposure (>4 years) was associated with reduced sVCAM-1 and sICAM-1. Conclusion: HIV and not traditional CVD risk factors is a primary contributor of monocyte/macrophage activation and inflammation despite ART. Anti-inflammatory therapies in addition to ART may be necessary to reduce these immune dysregulations and improve health outcomes of African PLWH. Abstract : Supplemental Digital Content is available in the text